A formação do professor leitor em duas gerações consecutivas - Berghetti, Ademar (2018)
The research focuses on the process of teacher training, contrasting a group of ten teachers who are starting their teaching activities, considering the period of up to five years, with another group of ten teachers, with twenty-five years or more of teaching. For this, the investigation was carried out in schools of the municipal education network of Marau / RS, with teachers of Childhood Education to the 9th year of Elementary School. Thus, this work aims to analyze the reading practice in teacher training in two consecutive generations, in order to identify the experiences lived in this process that delimited a more effective formation. In order to achieve the proposed objectives, it will be presented fundamentals about reading and its role within the school, highlighting its importance for the student's formation in the light of the thinking defended by several theorists of the area, among them: Regina Zilberman (2001), Marisa Lajolo (1997), Tania Mariza Kuchenbecker Rösing (2001), Michèle Petit (2008), Max Butlen (2012), Pierre Bourdieu and Roger Chartier (2001), who make up the theoretical framework. In this context, the research was developed based on the guiding question: Have there been significant changes in the training of reading teachers, from generation past to present, and, if so, what are they? And, as hypothesis for this question is that through the information obtained seeks to identify the occurre nce of significant changes in the context researched as hypothesis for this question is that through the information obtained seeks to identify the occurrence of significant changes in the context researched and, if the teachers who are entering the teaching profession are more prepared in relation to those who are at the end of the career. The research instrument consisted of the application of a questionnaire, which seems to be the most appropriate and practical for obtaining the information sought. The analysis of the teacher's reading trajectory was carried out based on some categories, such as the reading formation, the role of the reading mediators, the experiences and the preferences, the reading of the literature, the personal collection, the participation in cultural activities readers and the awareness of the relationship between reading and reading.